Diagnostic and prognostic value of long non-coding RNA PROX1‑AS1 and miR-647 expression in gastric cancer - E. A. Vetchinkina; A. I. Kalinkin; E. B. Kuznetsova; A. E. Kiseleva; E. A. Alekseeva; M. V. Nemtsova; I. V. Bure (Успехи молекулярной онкологии)
Introduction. Gastric cancer remains one of the most common cancers and has a high mortality rate worldwide. Epigenetic alternations of non-coding RNAs (ncRNAs), including microRNAs and long ncRNAs can contribute to its pathogenesis and progression, and could be potent diagnostic and prognostic biomarkers.Aim. Estimation of PROX1‑AS1 and miR-647 expression in gastric cancer and investigation of its clinical significance. Materials and methods. Tumor and adjacent normal tissues (n = 62), and sectional normal tissue samples (n = 5) were included in the study. The expression of the ncRNAs was quantified by reverse transcription-polymerase chain reaction assay.Results. We have reviled the significant difference in the PROX1‑AS1 expression in tumor (p = 0.002) and non-tumor tissues (p <0.001) obtained from gastric cancer patients in comparison with sectional gastric tissues without pathology. Pearson correlation analysis confirmed a negative correlation between PROX1‑AS1 and miR-647 in gastric cancer both in tumor (р <0,001) and adjacent normal tissues (р <0.001). Besides, expression of PROX1‑AS1 and miR-647 was associated with the size and extent of the primary tumor.Conclusion. The obtained results allow to suggest a potential prognostic value of PROX1‑AS1 and miR-647 in gastric cancer.